The Relationship Between Knowledge and Attitudes with Medication Adherence in Tuberculosis Patients in The UPTD Puskesmas Ciamis Work Area - Monica, Intan; Noviati, Elis; Endang Purwati, Ayu; Marliany, Heni; Kurniawan, Rudi (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Mycobacterium tuberculosis bacteria is an acute infection also known as tuberculosis disease. This disease will have a bad impact if not treated properly. Knowledge and attitude can affect adherence to the healing process, the patient's indiscipline can be caused by the lack of public knowledge and awareness about medication adherence is very important. To find out whether there is a relationship between knowledge and attitude and medication adherence in tuberculosis patients in the work area of UPTD Ciamis Health Center. Method: This type of study uses observational analytics with a cross sectional research design.The population in this study is 30 people, and the sampling technique in this study uses Total Sampling because the number of samples is the same as the population and the number of population is less than 100. Result: The results of the study showed that there was a relationship between knowledge and medication adherence to outcomes (p=0.003<α=0.005) and a relationship between attitude and medication adherence to medication and outcomes (p=0.011<α=0.005). Conclusion: In this study, almost all of the respondents had good knowledge, good attitude and good medication adherence, and there is a relationship between knowledge and attitude and adherence to taking medicine.